1980
DOI: 10.1073/pnas.77.9.5263
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate requirement for expression and stability of acetylcholine receptor on the surface of embryonic muscle cells in culture.

Abstract: We have investigated the significance of protein glycosylation for metabolism of acetylcholine receptors (AcChoR) in primary cultures of embryonic chicken muscle cells. Tunicamycin, a specific inhibitor of the glycosylation of asparagine residues on glycoproteins, decreased AcChoR accumulation and accelerated its degradation. In contrast, there was no evidence that tunicamycin treatment affected AcChoR biosynthesis, intracellular transport, or incorporation into surface membranes. Leupeptin, an inhibitor of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
2

Year Published

1982
1982
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 43 publications
3
33
2
Order By: Relevance
“…In accordance with these results, most, if not all, glycoproteins have been shown to exhibit reduced surface expression upon tunicamycin treatment. However, in contrast to our conclusion, in some cases reduction was explained by enhanced degradation; e.g., nonglycosylated acetylcholine receptor (35) and fibronectin (36) reportedly degrade more rapidly, although data are conflicting for the latter protein (37). Hastened degradation has been indicated also for the T25 glycoprotein (8).…”
Section: Immunological Functions Of the Nonglycosylated Mutant Antigencontrasting
confidence: 52%
“…In accordance with these results, most, if not all, glycoproteins have been shown to exhibit reduced surface expression upon tunicamycin treatment. However, in contrast to our conclusion, in some cases reduction was explained by enhanced degradation; e.g., nonglycosylated acetylcholine receptor (35) and fibronectin (36) reportedly degrade more rapidly, although data are conflicting for the latter protein (37). Hastened degradation has been indicated also for the T25 glycoprotein (8).…”
Section: Immunological Functions Of the Nonglycosylated Mutant Antigencontrasting
confidence: 52%
“…Decreased stability of nonglycosylated proteins has been reported for other ion channel proteins. Inhibition of N-linked glycosylation has been shown to reduce stability of acetylcholine receptor and Shaker K ϩ channel proteins (2,12,23). Although it is generally believed that N-linked glycosylation protects proteins from proteolytic degradation, the specific proteolytic system involved in the rapid degradation of nonglycosylated proteins is not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is generally believed that N-linked glycosylation protects proteins from proteolytic degradation, the specific proteolytic system involved in the rapid degradation of nonglycosylated proteins is not fully understood. The accelerated degradation of nonglycosylated acetylcholine receptor has been shown to involve an intracellular lysosomal proteolytic system (23). Recently, it was reported that the rapid degradation of nonglycosylated Shaker K ϩ channel protein involves cytoplasmic proteasomes (12).…”
Section: Discussionmentioning
confidence: 99%
“…In considering what effect this enhanced glycosylating ability of diabetic kidney might have on basement membrane collagen formation, the question of the importance of the addition of carbohydrate to the peptide chain is relevant. Several recent reports have indicated that, for many newly synthesized proteins, the addition of carbohydrate provides protection against intracellular proteolysis and that molecules not glycosylated turn over more rapidly [47][48][49]. Degradation prior to secretion has been shown to be an important regulator of fibroblast procollagen production [50]; if basement membrane collagen synthesis is similarly controlled, a higher degree of carbohydration might lead to a greater net production of this protein in diabetes.…”
Section: Discussionmentioning
confidence: 99%